The application of metacommunity theory to the management of riverine ecosystems - Patrick, Christopher J.; Anderson, Kurt E.; Brown, Brown L.; Hawkins, Charles P.; Metcalfe, Anya; Saffarinia, Parsa; Siqueira, Tadeu [UNESP]; Swan, Christopher M.; Tonkin, Jonathan D.; Yuan, Lester L. (Wiley, 2021)
River managers strive to use the best available science to sustain biodiversity and ecosystem function. To achieve this goal requires consideration of processes at different scales. Metacommunity theory describes how multiple species from different communities potentially interact with local-scale environmental drivers to influence population dynamics and community structure. However, this body of knowledge has only rarely been used to inform management practices for river ecosystems. In this article, we present a conceptual model outlining how the metacommunity processes of local niche sorting and dispersal can influence the outcomes of management interventions and provide a series of specific recommendations for applying these ideas as well as research needs. In all cases, we identify situations where traditional approaches to riverine management could be enhanced by incorporating an understanding of metacommunity dynamics. A common theme is developing guidelines for assessing the metacommunity context of a site or region, evaluating how that context may affect the desired outcome, and incorporating that understanding into the planning process and methods used. To maximize the effectiveness of management activities, scientists, and resource managers should update the toolbox of approaches to riverine management to reflect theoretical advances in metacommunity ecology. This article is categorized under: Water and Life > Nature of Freshwater Ecosystems Water and Life > Conservation, Management, and Awareness Water and Life > Methods.
Keywords: biomonitoring; conservation; dispersal; invasive species; local sorting; network connectivity; restoration; spatial